On circuit techniques to improve noise immunity of CMOS dynamic logic. - Li Ding (IEEE Transactions on VLSI systems)
Dynamic CMOS logic circuits are widely employed in high-performance VLSI chips in pursuing very high system performance. However, dynamic CMOS gates are inherently less resistant to noises than static CMOS gates. With the increasing stringent noise requirement due to aggressive technology scaling, the noise tolerance of dynamic circuits has to be first improved for the overall reliable operation of VLSI chips designed using deep submicron process technology. In the literature, a number of design techniques have been proposed to enhance the noise tolerance of dynamic logic gates. An overview and classification of these techniques are first presented in this paper. Then, we introduce a novel noise-tolerant design technique using circuitry exhibiting a negative differential resistance effect. We have demonstrated through analysis and simulation that using the proposed method the noise tolerance of dynamic logic gates can be improved beyond the level of static CMOS logic gates while the performance advantage of dynamic circuits is still retained. Simulation results on large fan-in dynamic CMOS logic gates have shown that, at a supply voltage of 1.6 V, the input noise immunity level can be increased to 0.8 V for about 10% delay overhead and to 1.0 V for only about 20% delay overhead.